Characterization of fracture aperture field heterogeneity by electrical resistance measurement - Boschan, Alejandro (2011)
We use electrical resistance measurements to characterize the aperture field in a rough fracture. This is done by performing displacement xperiments using two miscible fluids of different electrical resistivity and monitoring the time variation of the overall fracture resistance. Two fractures have been used: their complementary rough walls are identical but have different relative shear displacements which create “channel” or “barrier” structures in the aperture field, respectively parallel or perpendicular to the mean flow velocity →U. In the “channel” geometry, the resistance displays an initial linear variation followed by a tail part which reﬂects the velocity contrast between slow and fast ﬂow channels. In the “barrier” geometry, a change in the slope between two linear zones suggests the existence of domains of different characteristic aperture along the fracture. These variations are well reproduced analytically and numerically using simple ﬂow models. For each geometry, we present then a data inversion procedure that allows one to extract the key features of the heterogeneity from the resistance measurement.